Periodontal Ehlers-Danlos syndrome in early childhood: A case report of loss of deciduous teeth - Ricardo Souza Martins; Francisco Wilker Mustafa Gomes Muniz; Juliana Oliveira Gondim; Luísa De Souza Maurique; Clélia Maria Nolasco-Lopes; Bibiana Mello De Oliveira; Rosimary De Sousa Carvalho (Wolters Kluwer Medknow Publications, 2023)
The aim of the present study is to report a case of periodontal Ehlers-Danlos syndrome (pEDS) in early childhood. A 3-year-old child, complaining of severe tooth mobility, gingival bleeding, and early loss of deciduous teeth sought the dental clinics. The patient was diagnosed with pEDS, and no other systematic health impairments were diagnosed. It was implemented a strict supragingival biofilm control, using mechanical and chemical strategies. However, during the treatment, the patient had to receive multiple dental extractions. Scaling and root planing were performed in the remaining teeth, and the patient is included in the periodontal maintenance program to prevent recurrence of the disease. It was concluded that, although rare, severe cases of periodontitis may occur in deciduous teeth. Strict supragingival biofilm control and periodontal maintenance are strongly recommended in those patients, along with familial monitoring.